Synthesis and characterization of rapeseed oil bio-lubricant dispersed with nano copper oxide: Its effect on wear and frictional behavior of piston ring–cylinder liner combination. (November 2014) - Arumugam, S; Sriram, G
Direct application of vegetable oil as automotive lubricants is less favorable due to its poor thermo-oxidative stability, cold flow behavior, and poor anti-wear characteristics. The investigation detailed in this paper pertains to chemical modification of rapeseed oil through epoxidation, hydroxylation, and esterification processes in order to improve its thermo-oxidative stability and cold flow behavior. The copper oxide (CuO) nanoparticles of size ∼40–70 nm was dispersed in chemically modified rapeseed oil (CMRO) in three different concentrations (0.1 wt%, 0.5 wt%, and 1 wt%) as an anti-wear additive using an ultrasonic sonicator. The tribological behavior of cylinder liner against piston ring segment was tested with CMRO with and without CuO nano-additive using high frequency reciprocating rig tribometer. The morphological characterization of CuO nanoparticles dispersed in CMRO was done using scanning electron microscopy and X-ray diffraction analysis. The results were also compared with commercial synthetic lubricant under the same operating conditions. The atomic force microscopy and scanning electron microscopic analyses proved that the surface morphology of tested cylinder liner surfaces are smooth with optimum concentration of 0.5 wt% CuO nanoparticles dispersed in CMRO.